Ekspor Revolusi Islam dan Identitas Republik Islam Iran - Naldo Helmys (Department of International Relations, Universitas Andalas, 2016)
Having been considered as rational actor acting based on national interests, sovereign states is also understood have their own identities. Moreover, state identities have pivotal role on determining state behavior in international social structure. Stand on that assumption, this paper will describe the four state identities of Islamic Republic of Iran that assist to find an answer for interesting question: why did Iran export their Islamic Revolution throughout Middle East during Ayatollah Khomeini’s era (1979-1989)?During export of revolution, Iran was in war with Iraq and ideologically conflicted with Saudi while its fundamental ideology was spread across by propagating via international radio network and supporting oppressed nations in some countries. This historical phenomenon will be explained by Constructivism in International Relations, especially based on Alexander Wendt’s Social Theory of International Politics. It can be seen that there are four identities of Iran: as an Islamic Iran nation, velayat-e faqih-based Islamic Republic, core of Islamic world, and part of Pan-Islam.